The Government’s communication: Diffusion Innovation or Participatory Approach towards Renewable Energy Development Project - Gregoria Arum Yudarwati (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2023)
This study focuses on development communication in supporting Government’s renewable energy project in Indonesia. Using a case study of the communication in the implementation of a micro-hydro power plant (MHPP) project by Indonesia government, this study examines whether the government’s communication aims to encourage community participation in the project or merely diffuse the innovation for community’s adoption, or combine both approaches. This project was chosen, since this requires more community participation to maintain it as well as sustained communication to facilitate meaningful engagement. Appreciative inquiry involving six focus group discussions and nine in-depth interviews were conducted to explore communities’ experiences in exploiting the MHPP and accompanying communication process. The findings show that project development is divided into five stages: pre-initiation, initiation, adoption, transition and sustainability. Compared to the diffusion and adoption process, this project cycle is comparable to the five stages of the diffusion and adoption process. The information sharing session to introduce the innovation is significant to build awareness among communities. Likewise, the ideas to choose and train communities’ representatives as pioneers to the adoption process help communities gain direct experiences about the use of technology. Nevertheless, the domination of diffusion innovation approach with mechanistic communication that prioritises technological change may lead to a lack of participation and empowerment. Participatory approach that acknowledges local values will likely empower communities and build ownership towards the project.ABSTRAK Kajian ini fokus pada komunikasi pembangunan dalam mendukung proyek energi terbarukan Pemerintah di Indonesia. Dengan menggunakan studi kasus komunikasi dalam pelaksanaan proyek pembangkit listrik tenaga mikrohidro (PLTMH) yang dilakukan pemerintah Indonesia, penelitian ini mengkaji apakah komunikasi pemerintah bertujuan untuk mendorong partisipasi masyarakat dalam proyek tersebut atau sekadar menyebarkan inovasi agar dapat diadopsi oleh masyarakat, atau menggabungkan kedua pendekatan tersebut. Proyek ini dipilih karena memerlukan lebih banyak partisipasi masyarakat untuk memeliharanya serta komunikasi yang berkelanjutan untuk memfasilitasi keterlibatan yang bermakna. Metode appreciative inquiry yang melibatkan enam focus group discussions dan sembilan wawancara mendalam dilakukan untuk menggali pengalaman masyarakat dalam memanfaatkan PLTMH dan proses komunikasi yang menyertainya. Hasil penelitian menunjukkan bahwa pengembangan proyek dibagi menjadi lima tahap: pra-inisiasi, inisiasi, adopsi, transisi, dan keberlanjutan. Siklus proyek ini sebanding dengan lima tahap proses difusi dan adopsi. Sesi berbagi informasi untuk memperkenalkan inovasi ini penting untuk membangun kesadaran di kalangan masyarakat. Demikian pula, gagasan untuk memilih dan melatih perwakilan masyarakat sebagai pionir dalam proses adopsi membantu masyarakat mendapatkan pengalaman langsung tentang penggunaan teknologi. Meskipun demikian, dominasi pendekatan difusi inovasi dengan komunikasi mekanistik yang mengedepankan perubahan teknologi dapat menyebabkan kurangnya partisipasi dan pemberdayaan. Pendekatan partisipatif yang melibatkan nilai-nilai lokal akan dapat lebih memberdayakan masyarakat dan membangun kepemilikan terhadap proyek.